The K(+)–Cl(−) cotransporter KCC2 promotes GABAergic excitation in the mature rat hippocampus - Viitanen, Tero (Blackwell Science Inc, 2010)
GABAergic excitatory [K(+)](o) transients can be readily evoked in the mature rat hippocampus by intense activation of GABA(A) receptors (GABA(A)Rs). Here we show that these [K(+)](o) responses induced by high-frequency stimulation or GABA(A) agonist application are generated by the neuronal K(+)–Cl(−) cotransporter KCC2 and that the transporter-mediated KCl extrusion is critically dependent on the bicarbonate-driven accumulation of Cl(−) in pyramidal neurons. The mechanism underlying GABAergic [K(+)](o) transients was studied in CA1 stratum pyramidale using intracellular sharp microelectrodes and extracellular ion-sensitive microelectrodes. The evoked [K(+)](o) transients, as well as the associated afterdischarges, were strongly suppressed by 0.5–1 mm furosemide, a KCl cotransport inhibitor. Importantly, the GABA(A)R-mediated intrapyramidal accumulation of Cl(−), as measured by monitoring the reversal potential of fused IPSPs, was unaffected by the drug. It was further confirmed that the reduction in the [K(+)](o) transients was not due to effects of furosemide on the Na(+)-dependent K(+)-Cl(−) cotransporter NKCC1 or on intraneuronal carbonic anhydrase activity. Blocking potassium channels by Ba(2+) enhanced [K(+)](o) transients whereas pyramidal cell depolarizations were attenuated in further agreement with a lack of contribution by channel-mediated K(+) efflux. The key role of the GABA(A)R channel-mediated anion fluxes in the generation of the [K(+)](o) transients was examined in experiments where bicarbonate was replaced with formate. This anion substitution had no significant effect on the rate of Cl(−) accumulation, [K(+)](o) response or afterdischarges. Our findings reveal a novel excitatory mode of action of KCC2 that can have substantial implications for the role of GABAergic transmission during ictal epileptiform activity.